Analisis Hukum Islam: Keabsahan E-Commerce dan Hak Perlindungan Konsumen - Wiji Fitri Yanti; Widya Sari; Misra Misra (Sujud: Jurnal Agama, Sosial dan Budaya, 2026)
A trade activity through internet media is called as electronic commerce (e-commerce). Consumers who transact through the internet tend to cause losses caused by business actors. The e-commerce transaction process starts from promotional and marketing issues to selling, payment and contract making issues. The purpose of this study is to examine the law of protection for consumers in e-commerce transactions according to the Islamic view. The research method used in this study is a qualitative method with the data collection technique used is a literature study, namely a literature study with data sources from several book references and internet media related to the specific problems of this study. The results of this study show that business transactions through e-commerce are a new alternative in doing business in today's era. The transaction process through e-commerce according to Islam is declared valid if aspects of consumer protection can be guaranteed and proven in accordance with the rules that have been determined by the syara' and as long as they are not prohibited by sharia or contrary to the postulates